PKM Pengukuran Kadar Kolesterol Total dan Penyuluhan Kesehatan pada Lansia hipertensi di Puskesmas Cukir, Kabupaten Jombang - Arifin, Zainul; Sayekti, Sri (Yayasan Daarul Huda Kruengmane, 2024)
The factor that supports increasing total cholesterol is age. At the age of less than 60 years and above, cholesterol often increases, more precisely for elderly women under 60 years and for elderly men less than 70 years. A preliminary study of cholesterol levels in the elderly at Cukir Public Health Center, Jombang Regency, conducted by Vidayana, found that 59.38% (19 respondents) had cholesterol levels within the high risk threshold (200-240 mg/dl). The aim of community service is to determine cholesterol levels in elderly people with hypertension before and after being given health education in Jombang Regency. Total Cholesterol Measurement Method: CHOD- PAP. The population is 41 people. The sample consisted of 30 people using consecutivel sampling. The results of measurements before being given counseling showed that almost half of the respondents had high cholesterol levels, 12 respondents (40%), almost half of the respondents had slightly high cholesterol levels, 12 respondents (40%) had normal cholesterol levels. and 6 respondents (20%). After counseling, it was found that 10 respondents (33.3%), almost half of the respondents had slightly high cholesterol levels, 8 respondents (26.7%) had normal cholesterol levels. and 12 respondents (40%). Counseling can reduce cholesterol levels in the elderly. This Community Service shows the results of changes in cholesterol levels in the elderly.